Identifying Protein‐Protein Interactions by Proximity Biotinylation with AirID and splitAirID. Issue 3 (20th March 2023) - Schaack, Grace A.; Sullivan, Owen M.; Mehle, Andrew
Abstract: Proteins frequently function in high‐order complexes. Defining protein‐protein interactions is essential to acquiring a full understanding of their activity and regulation. Proximity biotinylation has emerged as a highly specific approach to capture transient and stable interactions in living cells or organisms. Proximity biotinylation exploits promiscuous biotinylating enzymes fused to a bait protein, resulting in the biotinylation of adjacent endogenous proteins. Biotinylated interactors are purified under very strict conditions and identified by mass spectrometry to obtain a high‐confidence list of candidate binding partners. AirID is a recently described biotin ligase specifically engineered for proximity labeling. This protocol details proximity biotinylation by AirID, using protein complexes that form during a type I interferon response as an example. It covers the construction and validation of AirID fusion proteins and the enrichment and identification of biotinylated interactors. We describe a variation on the protocol using splitAirID. In this case, AirID is split into two inactive fragments and ligase activity is only restored upon dimerization of the bait proteins. This permits selective detection of proteins that interact with homo‐ or heterodimeric forms of the bait. The protocol considers design strategies, optimization, and the properties of different biotin ligases to identify optimal conditions for each experimental question. We also discuss common pitfalls and how to troubleshoot them. These approaches allow proximity biotinylation to be a powerful tool for defining protein interactomes. © 2023 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Construction and functional validation of AirID fusion proteins Alternate Protocol : Construction and functional validation of splitAirID fusion proteins Support Protocol : Western blot for biotinylated proteins Basic Protocol 2 : Biotinylation, enrichment, and identification of protein interactors